Rh x Sb y CNT materials, their preparation methods, and applications

CN117254052BActive Publication Date: 2026-10-23INST OF NEW MATERIALS & IND TECH WENZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311275684.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2026-10-23
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

[0004]此外,Pt容易因痕量的一氧化碳(CO)气体(<10ppm)中毒而失活成为限制燃料电池大规模应用的瓶颈

Benefits of technology

[0032](1)本发明制备的CNT负载的RhxSby二元金属间化合物中,RhxSby纳米颗粒尺寸小,粒径均一、分散性良好,实现了严格的原子计量比,性能好,是具有高催化活性且稳定的二元金属间化合物电催化剂材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117254052B_ABST
    Figure CN117254052B_ABST
Patent Text Reader

Abstract

The application discloses Rh x Sb y / CNT material, a preparation method and application thereof. Rh x Sb y / CNT material is a carbon nanotube loaded Rh x Sb y binary intermetallic compound, wherein x:y = 1:1 or 2:1, wherein Rh x Sb y The nanoparticle size is small, the particle size is uniform, the dispersity is good, and strict atomic stoichiometric ratio is realized. Rh x Sb y / CNT material exhibits excellent HOR activity, is far superior to metal Rh and commercial Pt / C com performance, has excellent stability and very excellent CO tolerance in use, and can be used as a HOR catalyst, in particular, as an anode HOR catalyst of an alkaline exchange membrane fuel cell. Meanwhile, the preparation method is simple, the cost is low, and the application is conducive to popularization and use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanomaterials and electrochemical energy technology, specifically relating to binary intermetallic compound materials and their preparation and application. Background Technology

[0002] Hydrogen-oxygen fuel cells (HFCs) are a green and efficient energy conversion technology that directly converts hydrogen energy into electrical energy, and are considered one of the key technologies leading the future of energy. Alkaline membrane fuel cells (AEMFCs) have promising commercial applications due to their low cost, mild operating conditions, and large-area processing capabilities. In particular, the commercialization of AEMFCs has become possible with the rapid development of anion exchange membrane technology and the ample supply of high-performance non-precious metal cathode oxygen reduction reaction (ORR) catalysts in alkaline media. However, compared with the hydrogen oxidation reaction (HOR) at the anode in PEMFCs, the kinetics of the anode HOR in AEMFCs are significantly reduced. Therefore, there is an urgent need to develop low-cost, highly active, and stable alkaline media HOR catalysts.

[0003] Currently, commercially available HOR catalysts are platinum group metal catalysts. However, platinum (Pt) itself is expensive and highly sensitive to the presence of contaminants, making it susceptible to poisoning. Most platinum group elements are known to exhibit high activity in HOR reactions. Commercially available HOR catalysts are carbon-supported platinum group metals, such as Pt / C, Ru / C, Pd / C, Ir / C, and Rh / C. Currently, in terms of mass activity, Ru-based electrocatalysts (PtRu, IrRu, and PdIrRu) are the most active electrocatalysts for alkaline HOR. HOR activity is sensitive to various structural parameters of platinum group metal electrocatalysts in alkaline media, including size, morphology, composition, and support. Changing structural parameters can adjust the alkaline HOR activity of platinum group metal electrocatalysts. Therefore, we can prepare low-platinum catalysts by changing the size, morphology, composition, and support of the catalyst. For example, the mass activity and specific activity of platinum group metal catalysts such as Ir / C, Ru / C, Pt / C, and Pd / C exhibit different changing patterns with particle size. This is attributed to structural characteristics. Different noble metals and their particles of different sizes have different proportions of unsaturated coordinating atoms, crystal faces with defined crystal indices, amorphous structures, and defects, which can control and alter the HOR catalytic activity, potentially leading to the preparation of low-platinum catalysts. For example, some papers report that Pt nanowires exhibit higher alkaline HOR performance than commercial Pt / C, suggesting that one-dimensional nanomaterials may enhance alkaline HOR activity due to the presence of crystal facet fragments, fewer defect sites, and a high aspect ratio. For Ru-Pt core-shell electrocatalysts, morphology also influences alkaline HOR activity. The specific activity of Pt in two-layer and single-layer Pt shells in alkaline solutions is 3.1 times and 2.3 times that of Pt nanocatalysts, respectively. Furthermore, the composition of the electrocatalyst is closely related to the alkaline HOR activity. Adding other transition metals can improve catalytic performance by influencing ligands and strain effects, which is also a pathway for preparing low-platinum catalysts. MEScofield et al. synthesized Pt7M3 alloy nanowires (M = Ru, Fe, Co, Cu, Au) for a study on the correlation between chemical composition and basic HOR activity. They confirmed that the PtM alloy nanowire catalyst improved the activity of the hydrogen oxidation reaction (HOR) compared to commercially available Pt standards and the synthesized Pt NWs. The high basic HOR activity was attributed to the favorable synergistic effect of electronic interactions between Pt and the second metal, as well as the deformation-strain effect, confirming a clear and correlated dependence between HOR activity and chemical composition. It is certain that the activity of basic HOR can be rationally tuned by changing the composition of the electrocatalyst. Furthermore, the presence of a support may also have a beneficial effect on the basic HOR activity of platinum group metal electrocatalysts; low-platinum catalysts can also be obtained by changing or modifying the support.

[0004] Furthermore, Pt is easily deactivated by trace amounts of carbon monoxide (CO) gas (<10 ppm), which is a bottleneck limiting the large-scale application of fuel cells. Commercial hydrogen is mainly derived from steam reforming, but CO is inevitably present in the reforming products, affecting catalytic performance. Purifying inexpensive crude hydrogen to meet the requirements of fuel cells would undoubtedly increase the complexity and cost of the equipment. Therefore, developing catalysts with high activity, good stability, and resistance to CO toxicity is another practical way to solve the above problems. Summary of the Invention

[0005] In view of this, the present invention provides an Rh x Sb y / CNT materials, their preparation methods, and applications. Rh x Sb y / CNT material is Rh supported by carbon nanotubes x Sb y Binary intermetallic compounds possess high catalytic activity and stability, as well as resistance to CO toxicity, and can be used as highly efficient anode HOR catalysts for alkaline exchange membrane fuel cells.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] In a first aspect of the invention, a Rh is provided x Sb y / CNT material, Rh supported by carbon nanotubes x Sb y Binary intermetallic compounds, where x:y = 1:1 or 2:1.

[0008] In some specific embodiments of the present invention, the Rh x Sb y Binary intermetallic compounds belong to the orthorhombic crystal system with space group Pnma(62).

[0009] In some specific embodiments of the present invention, the Rh x Sb y In binary intermetallic compounds, the direction of electron transfer is from Sb to Rh.

[0010] In a second aspect of the invention, the Rh is provided x Sb y The preparation method of / CNT material includes the following steps:

[0011] (1) Carbon nanotubes were ultrasonically dispersed in an ethanol aqueous solution, and then a RhCl3 / EtOH solution with a concentration of 0.1 mol / L was added and stirred for 10-60 min. NH4HCO3 was then added and stirring was continued for 2-10 h. The resulting suspension was centrifuged, washed, and freeze-dried to obtain a black solid. The black solid was then calcined at 600 °C for 1-3 h under a H2 / Ar reducing atmosphere and cooled to obtain Rh / CNT. The ratio of carbon nanotubes to Rh was 1.25-20 mmol of Rh per gram of carbon nanotubes.

[0012] (2) Take an appropriate amount of the Rh / CNT and ultrasonically disperse it in deionized water to obtain an Rh / CNT suspension; immerse SbCl3 in deionized water and ultrasonically disperse it to prepare an SbCl3 aqueous suspension; mix the SbCl3 aqueous suspension with the Rh / CNT suspension to obtain a mixed suspension, wherein the molar ratio of Rh to Sb in the feed is 2:1.8 or 1:1.2;

[0013] (3) After stirring the mixed suspension for 30–90 min, evaporate and dry it at 80–120 °C, and collect the black precipitate; calcine the obtained black precipitate at 800 °C for 1–4 h under a H2 / Ar reducing atmosphere, and cool it to obtain the Rh. x Sb y / CNT material.

[0014] Preferably, in step (1), the volume ratio of H2O to EtOH in the ethanol aqueous solution is 1:1.

[0015] Preferably, in step (1), the concentration of the carbon nanotubes in the ethanol aqueous solution is 0.1 to 3 g / L.

[0016] Preferably, in step (1), the mass ratio of NH4HCO3 to carbon nanotubes is 2.5 to 30:1.

[0017] Preferably, in step (1), the centrifugation speed of the suspension is 8000 to 15000 rpm.

[0018] Preferably, in step (1), the heating rate during calcination is 3 to 8 °C / min, more preferably 5 °C / min.

[0019] Preferably, in step (1), the volume percentage of H2 in the H2 / Ar reducing atmosphere is 5%-40%, more preferably 20%.

[0020] Preferably, in step (2), the concentration of Rh / CNT in the Rh / CNT suspension is 0.4 to 24 g / L.

[0021] Preferably, in step (2), the concentration of SbCl3 in the SbCl3 aqueous suspension is 0.1 to 32 g / L.

[0022] Preferably, in step (3), the stirring speed of the suspension is 200 to 1000 rpm.

[0023] Preferably, in step (3), the volume percentage of H2 in the H2 / Ar reducing atmosphere is 5%-40%, preferably 20%.

[0024] Preferably, in step (3), the heating rate during calcination is 3 to 8 °C / min, and more preferably 5 °C / min.

[0025] Preferably, in step (3), the cooling is natural cooling in the air.

[0026] In a third aspect of the invention, the Rh is provided x Sb y Application of CNT materials as catalysts in the hydrogenation reaction under alkaline media.

[0027] In some specific embodiments of the present invention, the Rh x Sb y / CNT materials are used as HOR catalysts in alkaline exchange membrane fuel cells.

[0028] In some specific embodiments of the present invention, the Rh x Sb y Application of CNT materials as catalysts against CO toxicity in the hydrogenation reaction under alkaline media.

[0029] In some specific embodiments of the present invention, the Rh x Sb y / CNT materials are used as HOR catalysts to resist CO toxicity in alkaline exchange membrane fuel cells.

[0030] In this invention, binary intermetallic compounds (BIMC), also known as atomically ordered alloys, refer to compounds formed by combining two metallic elements in different stoichiometric ratios. They have a regular surface or near-surface atomic ordered arrangement structure and unique electronic properties, and exhibit unique physicochemical properties that are different from those of the constituent metallic elements.

[0031] Compared with the prior art, the present invention has the following beneficial technical effects:

[0032] (1) Rh-loaded CNTs prepared in this invention x Sb y In binary intermetallic compounds, Rhx Sb y Nanoparticles are small in size, uniform in particle size, and well dispersed, achieving a strict atomic stoichiometry and exhibiting good performance. They are stable binary intermetallic compound electrocatalyst materials with high catalytic activity.

[0033] (2) The catalytic activity of the Rh2Sb / CNT prepared in this invention is compared with that of Rh / CNT and Pt / C com The HOR activity was increased by 17 times and 8 times respectively, demonstrating excellent performance, far superior to metallic Rh and commercial Pt / C. com The RhSb / CNTs prepared in this invention exhibit excellent stability and outstanding CO tolerance during use. Furthermore, they demonstrate very strong CO poisoning resistance and outstanding HOR catalytic activity, significantly superior to metallic Rh and commercially available Pt / C. com Performance.

[0034] (3) Rh2Sb / CNT and RhSb / CNT can be used as HOR catalysts, especially as HOR catalysts resistant to CO toxicity, and applied in the hydrogenation reaction under alkaline medium such as alkaline exchange membrane fuel cells.

[0035] (4) The preparation method of the present invention is simple and low in cost, which is conducive to its widespread use. Attached Figure Description

[0036] Figure 1 The image shows the XRD pattern of the Rh2Sb / CNT catalyst prepared in Example 1.

[0037] Figure 2 TEM image of the Rh2Sb / CNT catalyst prepared in Example 1.

[0038] Figure 3 This is a particle size analysis diagram of the Rh2Sb / CNT catalyst prepared in Example 1.

[0039] Figure 4 The image shows an HR-TEM image of the Rh2Sb / CNT catalyst prepared in Example 1.

[0040] Figure 5 The image shows the EDS and energy dispersive spectroscopy (EDS) analysis results of the Rh2Sb / CNT catalyst prepared in Example 1.

[0041] Figure 6 The image shows the XRD pattern of the RhSb / CNT catalyst prepared in Example 2.

[0042] Figure 7 This is a TEM image of the RhSb / CNT catalyst prepared in Example 2.

[0043] Figure 8This is a particle size analysis diagram of the RhSb / CNT catalyst prepared in Example 2.

[0044] Figure 9 The image shows an HR-TEM image of the RhSb / CNT catalyst prepared in Example 2.

[0045] Figure 10 The image shows the EDS and energy dispersive spectroscopy (EDS) analysis results of the RhSb / CNT catalyst prepared in Example 2.

[0046] Figure 11 The XRD pattern of the RhSb2 / CNT catalyst prepared for Comparative Example 1.

[0047] Figure 12 TEM image of the RhSb2 / CNT catalyst prepared for Comparative Example 1.

[0048] Figure 13 Particle size analysis diagram of the RhSb2 / CNT catalyst prepared for Comparative Example 1.

[0049] Figure 14 HR-TEM image of the RhSb2 / CNT catalyst prepared for Comparative Example 1.

[0050] Figure 15 EDS and energy dispersive spectroscopy (EDS) spectra of the RhSb2 / CNT catalyst prepared for Comparative Example 1.

[0051] Figure 16 The XRD pattern of the Rh / CNT catalyst prepared in Comparative Example 2 is shown.

[0052] Figure 17 TEM image of the Rh / CNT catalyst prepared in Comparative Example 2.

[0053] Figure 18 HR-TEM image of the Rh / CNT catalyst prepared for Comparative Example 2.

[0054] Figure 19 High-resolution XPS images of Sb in the Rh2Sb / CNT prepared in Example 1, the RhSb / CNT prepared in Example 2, and the RhSb2 / CNT material prepared in Comparative Example 1.

[0055] Figure 20 High-resolution XPS images of Rh in the Rh2Sb / CNT prepared in Example 1 and Example 2, and the RhSb2 / CNT prepared in Comparative Example 1 and Rb / CNT prepared in Comparative Example 2.

[0056] Figure 21 The four materials used in Examples 1 and 2, Comparative Examples 1 and 2, and the control material Pt / C comHORLSV curve of the catalyst.

[0057] Figure 22 The four materials used in Examples 1 and 2, Comparative Examples 1 and 2, and the control material Pt / C com Tafel plot of the catalyst.

[0058] Figure 23 The four materials used in Examples 1 and 2, Comparative Examples 1 and 2, and the control material Pt / C com The KL equation diagram for the catalyst at an overpotential of 50 mV vs. RHE.

[0059] Figure 24 The H of the four materials in Examples 1 and 2 and Comparative Examples 1 and 2 of this invention is used to fit the H of the materials in Examples 1 and 2. upd ECSA histogram of desorption peak area.

[0060] Figure 25 The four materials used in Examples 1 and 2 and Comparative Examples 1 and 2 of this invention, as well as the control material Pt / C, are examples of materials used in this invention. com A bar chart comparing catalyst loading and ECSA normalized exchange current density (50 mV vs. RHE).

[0061] Figure 26 The four materials used in Examples 1 and 2 and Comparative Examples 1 and 2 of this invention, as well as the control material Pt / C, are examples of materials used in this invention. com A bar chart comparing catalyst loading and ECSA normalized kinetic current density (50 mV vs. RHE).

[0062] Figure 27 The present invention relates to Rh2Sb / CNT and Rh / CNT, as well as the control material Pt / C. com The chronoamperometric response curve of the catalyst in H2-saturated 0.1M KOH with an overpotential of 0.1V vs. RHE.

[0063] Figures 28a-28e The four materials used in Examples 1 and 2 and Comparative Examples 1 and 2 of this invention, as well as the control material Pt / C, are examples of materials used in this invention. com HOR LSV curves of catalysis in 0.1M KOH solutions saturated with H2 / 1000ppm CO (solid line) and H2 saturated (dashed line).

[0064] Figure 29 The present invention relates to Rh2Sb / CNT and Rh / CNT, as well as the control material Pt / C. com The chronoamperometric response curves of the catalyst in 0.1M KOH saturated with H2 / 1000ppm CO with an overpotential of 100mV vs. RHE were obtained. Detailed Implementation

[0065] To better illustrate the present invention and facilitate understanding of its technical solutions, the present invention will be clearly, thoroughly, and completely described below with reference to embodiments. Obviously, the described embodiments are only a part of the embodiments of this application, not all of them. The illustrative drawings and embodiments are for the purpose of illustrating the present invention only and do not constitute any limitation on the actual scope of protection of the present invention, nor are they intended to limit the scope of protection of the present invention to these embodiments.

[0066] Unless otherwise specified, all reagents and instruments used in the following examples are commercially available products. For example, carbon nanotubes (CNTs) were carboxylated multi-walled carbon nanotubes, purchased from Xianfeng Nanomaterials Technology Co., Ltd.; rhodium chloride hydrate (RhCl3·H2O), ammonium bicarbonate, and ethanol were purchased from Aladdin Biochemical Technology Co., Ltd.; antimony chloride was purchased from Alfaesa Reagents Co., Ltd.; deionized water (18.2 MΩ / cm) used in all experiments was prepared using an ultrapure purification system; and the relevant gases required for the experiments were purchased from Wenzhou Longwan Changsheng Gas Co., Ltd.

[0067] Example 1: Preparation of Rh2Sb / CNT

[0068] (1) 40 mg of carbon nanotubes (CNTs) were dispersed in 80 mL of ethanol-water solution (H2O to EtOH volume ratio of 1:1) and ultrasonically dispersed for 40 min. 2 mL of a 0.1 mol / L RhCl3 / EtOH solution was added, and the mixture was stirred at 600 rpm for 30 min. Then, 400 mg of NH4HCO3 was added, and the mixture was stirred for 5 h. The resulting suspension was centrifuged at 12,000 rpm, washed, and freeze-dried to obtain a black solid. Finally, the solid was calcined at 600 °C for 2 h (heating rate of 5 °C / min) in a H2 / Ar reducing atmosphere (H2 / Ar volume ratio of 20:80) at a flow rate of 100 sccm, and then cooled to obtain Rh / CNTs.

[0069] (2) 8.0 mg of Rh / CNT was dispersed in 3 mL of deionized water and ultrasonically dispersed for 40 min to obtain an Rh / CNT suspension; 2.40 mg of SbCl3 was immersed in 2 mL of deionized water solvent and ultrasonically prepared to obtain an SbCl3 aqueous suspension; the above SbCl3 aqueous suspension and the above Rh / CNT suspension were mixed to obtain a mixed suspension. In this step, the molar ratio of Rh to Sb was 2:1.8.

[0070] (3) The mixed suspension was stirred at 600 rpm for 60 min, then evaporated and dried at 100 °C, and the black precipitate was collected. The obtained black precipitate was calcined at 800 °C for 3 h (heating rate of 5 °C / min) under the protection of 100 sccm of H2 / Ar mixed reducing gas (H2 / Ar volume ratio of 20:80), and then cooled to obtain the first material.

[0071] Structural characterization:

[0072] X-ray diffraction (XRD) analysis was performed on the first material obtained in Example 1, such as... Figure 1 As shown, its diffraction peaks are consistent with the standard PDF card 47-1302 of Rh2Sb, and there are no other compound or metal impurity phase peaks, indicating that it is a pure phase rhodium antimonide binary intermetallic compound Rh2Sb / CNT. Figure 1 The inset above shows a schematic diagram of the structure of Rh2Sb, illustrating that it is an orthorhombic crystal structure in the Pnma(62) space group.

[0073] The first material obtained in Example 1 was analyzed by transmission electron microscopy (TEM), such as... Figure 2 As shown, the Rh2Sb nanoparticles are relatively uniformly dispersed and uniformly loaded on the surface of CNTs.

[0074] The particle size analysis of the first material obtained in Example 1 was performed, such as... Figure 3 As shown, the particle size of Rh2Sb nanoparticles exhibits a normal distribution, with a particle size of 9.8±2.2 nm, indicating that the particle size of Rh2Sb nanoparticles is relatively small.

[0075] The first material obtained in Example 1 was analyzed by high-resolution transmission electron microscopy (HR-TEM), such as... Figure 4 As shown, individual Rh₂Sb particles exhibit clear lattice fringes, with a lattice spacing of [missing information]. and It corresponds to its (210) and (020) crystal planes respectively, and the electron beam of Rh2Sb is along the

[001] direction during TEM imaging.

[0076] The first material obtained in Example 1 was subjected to energy-dispersive X-ray elemental mapping (EDS) and energy-dispersive X-ray spectroscopy analysis, such as... Figure 5 As shown, Rh and Sb elements are uniformly distributed in a single nanoparticle in the first material, and the ratio of Rh to Sb atoms is 2:1, which verifies the XRD results and also indicates that it is a pure phase catalyst.

[0077] In summary, the first material obtained in Example 1 is a binary intermetallic compound Rh2Sb nanoparticle with an ordered structure, uniformly dispersed and loaded on carbon nanotubes.

[0078] Example 2: Preparation of RhSb / CNT

[0079] (1) 40 mg of carbon nanotubes were dispersed in 80 mL of ethanol-water solution (H2O to EtOH volume ratio of 1:1) and ultrasonically dispersed for 40 min. 2 mL of a 0.1 mol / L RhCl3 / EtOH solution was added, and the mixture was stirred at 600 rpm for 30 min. Then, 400 mg of NH4HCO3 was added, and the mixture was stirred for 5 h. The resulting suspension was centrifuged at 12,000 rpm, washed, and freeze-dried to obtain a black solid. Finally, the solid was calcined at 600 °C for 2 h (heating rate of 5 °C / min) in a H2 / Ar reducing atmosphere (H2 / Ar volume ratio of 20:80) at a flow rate of 100 sccm, and then cooled to obtain Rh / CNTs.

[0080] (2) 8.0 mg of Rh / CNT was dispersed in 3 mL of deionized water and ultrasonically dispersed for 40 min to obtain an Rh / CNT suspension; 3.19 mg of SbCl3 was immersed in 2 mL of deionized water solvent and ultrasonically prepared to obtain an SbCl3 aqueous suspension; the above SbCl3 aqueous suspension and the above Rh / CNT suspension were mixed to obtain a mixed suspension. In this step, the molar ratio of Rh to Sb was 1:1.2.

[0081] (3) The mixed suspension was stirred at 600 rpm for 60 min, then evaporated and dried at 100 °C, and the black precipitate was collected. The obtained black precipitate was calcined at 800 °C for 3 h (heating rate of 5 °C / min) under the protection of 100 sccm of H2 / Ar mixed reducing gas (H2 / Ar volume ratio of 20:80), and then cooled to obtain the second material.

[0082] Structural characterization:

[0083] XRD analysis was performed on the second material obtained in Example 2, such as... Figure 6 As shown, its diffraction peaks are consistent with the standard PDF card 34-0331 of RhSb, and there are no other compound or metal impurity phase peaks, indicating that it is a pure phase rhodium antimonide binary intermetallic compound RhSb / CNT. Figure 6 The illustration above shows the structure of RhSb, indicating that it is an orthorhombic crystal structure in the Pnma(62) space group.

[0084] TEM analysis was performed on the second material obtained in Example 2, such as... Figure 7 As shown, the RhSb nanoparticles are relatively uniformly dispersed and uniformly loaded on the surface of CNTs.

[0085] The particle size analysis of the second material obtained in Example 2 was performed, such as... Figure 8 As shown, the particle size of RhSb nanoparticles exhibits a normal distribution, with a particle size of 9.4 ± 2.3 nm, indicating that the particle size of RhSb nanoparticles is relatively small.

[0086] The second material obtained in Example 2 was subjected to HR-TEM analysis, such as... Figure 9 As shown, individual RhSb particles exhibit clear lattice fringes, with a lattice spacing of [missing information]. and They correspond to their (201) and (022) crystal planes respectively; and RhSb during TEM imaging, the electron beam along... direction.

[0087] The second material obtained in Example 2 was subjected to EDS and energy dispersive spectroscopy analysis, such as... Figure 10 As shown, the Rh and Sb elements in the second material are uniformly distributed in a single nanoparticle, and the ratio of Rh to Sb atoms is 1:1, which verifies the XRD results and also indicates that it is a pure phase catalyst.

[0088] In summary, the second material obtained in Example 2 is a binary intermetallic compound RhSb nanoparticle with an ordered structure, uniformly dispersed and loaded on carbon nanotubes.

[0089] Comparative Example 1: Preparation of RhSb2 / CNT

[0090] (1) 40 mg of carbon nanotubes (CNTs) were dispersed in 80 mL of ethanol-water solution (H2O to EtOH volume ratio of 1:1) and ultrasonically dispersed for 40 min. 2 mL of a 0.1 mol / L RhCl3 / EtOH solution was added, and the mixture was stirred at 600 rpm for 30 min. Then, 400 mg of NH4HCO3 was added, and the mixture was stirred for 5 h. The resulting suspension was centrifuged at 12,000 rpm, washed, and freeze-dried to obtain a black solid. Finally, the solid was calcined at 600 °C for 2 h (heating rate of 5 °C / min) in a H2 / Ar reducing atmosphere (H2 / Ar volume ratio of 20:80) at a flow rate of 100 sccm, and then cooled to obtain Rh / CNTs.

[0091] (2) 8.0 mg of Rh / CNT was dispersed in 3 mL of deionized water and ultrasonically dispersed for 40 min to obtain an Rh / CNT suspension; 30.68 mg of SbCl3 was immersed in 2 mL of deionized water solvent and ultrasonically prepared to obtain an SbCl3 aqueous suspension; the above SbCl3 aqueous suspension and the above Rh / CNT suspension were mixed to obtain a mixed suspension. In this step, the molar ratio of Rh to Sb was 1:10.

[0092] (3) The mixed suspension was stirred at 600 rpm for 60 min, then evaporated and dried at 100 °C, and the black precipitate was collected. The obtained black precipitate was calcined under the protection of 100 sccm of H2 / Ar mixed reducing gas (H2 / Ar volume ratio of 20:80), heated to 800 °C and held for 3 h (heating rate of 5 °C / min), and then cooled to obtain the third material.

[0093] Structural characterization:

[0094] XRD analysis was performed on the third material obtained in Comparative Example 1, such as... Figure 11 As shown, its diffraction peaks are consistent with the standard PDF card 14-0495 for RhSb2, and there are no other compound or metal impurity phase peaks, indicating that it is a pure phase rhodium distigmine binary intermetallic compound RhSb2 / CNT. Figure 11 The illustration above shows the structure of the RhSb2 phase, indicating that it is a monoclinic crystal structure in space group P21 / c(14).

[0095] TEM analysis was performed on the third material obtained in Comparative Example 1, such as... Figure 12 As shown, the RhSb2 nanoparticles are relatively uniformly dispersed and uniformly loaded on the surface of CNTs.

[0096] The particle size analysis of the third material obtained in Comparative Example 1 was performed, such as... Figure 13 As shown, the particle size of RhSb2 nanoparticles exhibits a normal distribution, with a particle size of 10.2 ± 1.9 nm, indicating that the particle size of RhSb2 nanoparticles is relatively small.

[0097] HR-TEM analysis was performed on the third material obtained in Comparative Example 1, such as... Figure 14 As shown, individual RhSb2 particles exhibit clear lattice fringes, with a lattice spacing of [missing information]. and Corresponding to its (020) and (111) crystal planes respectively; and RhSb2 during TEM imaging, the electron beam along direction.

[0098] EDS and energy dispersive spectroscopy analyses were performed on the third material obtained in Comparative Example 1, such as... Figure 15 As shown, Rh and Sb elements are uniformly distributed in a single nanoparticle in the third material, and the ratio of Rh to Sb atoms is 1:2, which verifies the XRD results and also indicates that it is a pure-phase catalyst.

[0099] In summary, the third material obtained in Comparative Example 1 consists of ordered binary intermetallic compound RhSb2 nanoparticles uniformly dispersed and loaded on carbon nanotubes.

[0100] Comparative Example 2: Preparation of Rh / CNT

[0101] 40 mg of carbon nanotubes (CNTs) were dispersed in 80 mL of an ethanol-water solution (H₂O to EtOH volume ratio of 1:1) and ultrasonically dispersed for 40 min. Then, 2 mL of a 0.1 mol / L RhCl₃ / EtOH solution was added, and the mixture was stirred at 600 rpm for 30 min. Next, 400 mg of NH₄HCO₃ was added, and the mixture was stirred for 5 h. The resulting suspension was centrifuged at 12,000 rpm, washed, and freeze-dried to obtain a black solid. Finally, the solid was calcined at 600 °C for 2 h (heating rate of 5 °C / min) in a H₂ / Ar reducing atmosphere (H₂ / Ar volume ratio of 20:80) at a flow rate of 100 sccm, and then cooled to obtain the fourth material.

[0102] Structural characterization:

[0103] XRD analysis was performed on the fourth material obtained in Comparative Example 2, such as... Figure 16 As shown, its diffraction peaks are consistent with the standard PDF card 87-0714 of Rh, with obvious peaks at 41.1°, 47.8°, 69.9° and 84.4°, which belong to the (111), (200), (220) and (311) crystal planes of fcc Rh nanoparticles, respectively.

[0104] TEM analysis was performed on the fourth material obtained in Comparative Example 2, such as... Figure 17 As shown, the Rh metal nanoparticles are relatively uniformly dispersed and uniformly loaded on the surface of CNTs.

[0105] HR-TEM analysis was performed on the fourth material obtained in Comparative Example 2, such as... Figure 18 As shown, individual Rh particles exhibit clear lattice fringes, with a lattice spacing of [missing information]. It corresponds to its (111) crystal plane.

[0106] In summary, the fourth material obtained in Comparative Example 2 is Rh nanoparticles uniformly dispersed and loaded on carbon nanotubes.

[0107] The following is a comparative analysis of the first and second materials obtained from Examples 1 and 2 and the third and fourth materials obtained from Comparative Examples 1 and 2.

[0108] I. High-resolution X-ray photoelectron spectroscopy (XPS) detection and analysis.

[0109] The surface electronic properties and chemical states of each material were investigated using XPS spectroscopy. Peak values ​​for all metal elements were observed in the XPS spectra of the four catalyst materials, with the C peak at 284.6 eV used as a reference to correct for charge effects.

[0110] Figure 19 High-resolution XPS images of Sb in Rh2Sb / CNT, RhSb / CNT, and RhSb2 / CNT materials are shown. The images reveal that Sb exhibits a metallic state. 0 ) and a small portion of the oxidation state (Sb 3+ ) dominates; O is observed at 530.2 and 531.8 eV. Ⅰ and O Ⅱ Two characteristic peaks, which are attributed to lattice oxygen and hydroxyl groups in the metal oxide, respectively. Sb 0 3D 5 / 2 The binding energies in Rh2Sb / CNT, RhSb / CNT, and RhSb2 / CNT were 528.9 eV, 528.8 eV, and 528.7 eV, respectively, indicating that Rh2Sb / CNT, RhSb / CNT, and RhSb2 / CNT exhibit different Sb binding energies. 0 3D 5 / 2 The electronic state.

[0111] Figure 20 High-resolution XPS images of Rh in Rh2Sb / CNT, RhSb / CNT, and RhSb2 / CNT materials are shown. The images reveal that Rh exhibits a metallic state. 0 ) and a small portion of the oxidized state (Rh 3+ ) dominates. Rh 0 3D 5 / 2 The binding energies in Rh, Rh₂Sb, RhSb, and RhSb₂ are 307.70 eV, 307.35 eV, 307.52 eV, and 307.59 eV, respectively; and the binding energies with metallic Rh₂Sb ... 0 3D 5 / 2 Compared to the binding energy of 307.7 eV, the binding energies of Rh₂Sb / CNT, RhSb / CNT, and RhSb₂ / CNT are negatively shifted by 0.35, 0.18, and 0.11 eV, respectively. This indicates that Rh₂Sb / CNT, RhSb / CNT, and RhSb₂ / CNT exhibit different Rh orbital binding energies. 0 3D 5 / 2 The electronic state.

[0112] It can be seen that the Rh2Sb or RhSb binary intermetallic compounds in Examples 1 and 2 have different surface electron distributions than the RhSb2 binary intermetallic compound in Comparative Example 1.

[0113] II. Catalytic performance testing

[0114] Key parameters involved in catalytic activity assessment include the apparent current density (j0) normalized to electrode geometry, electrochemically active surface area (ECSA), and the area-to-mass kinetic current density (j0) at a given overpotential (typically a relatively low overpotential, 50 mV). k,s and j k,m ), area ratio and mass ratio exchange current density (j 0,s and j 0,m )wait.

[0115] In this invention, ECSA is achieved using CO stripping voltammetry and H2O. upd The method of measurement mainly utilizes the adsorption and desorption of CO monolayers and metal H atoms on the metal surface to quantify the specific surface area, which is calculated using Equations 1 and 2.

[0116]

[0117] Wherein, S / V is obtained by electrochemical measurement of the electron transfer amount in the selected peak region and calculated by Equation 2:

[0118]

[0119] In the above formula, S is the integrated peak area, V is the scan rate, M is the metal loading, and Q is the charge density when the electrode surface is monolayer adsorbed (this value varies for different metals, such as Pt or Rh).

[0120] The measured total current density (j) is the dynamic current density (j) k ) component and diffusion current density (j d The combination of components can be described by the Koutecky-Levich (KL) equation, as shown in equation (3).

[0121]

[0122] Under infinitely fast reaction kinetics, the overpotential is completely diffusion-controlled; the diffusion-controlled overpotential (η) d It can be described by equation (4).

[0123]

[0124] Where R is the ideal gas constant, 8.314 J mol. -1 K -1 T is the thermodynamic temperature, and F is the Faraday constant 96,485 Cmol. -1 j l This is the H2 limiting current density. In RDE measurements, jl It is proportional to the square root of the rotational speed (ω), as expressed by the Levich equation (as shown in Equation 5):

[0125] j1=B C0ω 1 / 2 =0.62nFD 2 / 3 ν-1 / 6C0ω 1 / 2 ……………Equation (5)

[0126] Where B represents the Levich constant, C0 is the concentration of H2 in the electrolyte, n is the number of electrons transferred in the reaction, ν is the kinematic viscosity of the electrolyte, ω is the rotational speed of the rotating disk electrode, and D is the diffusion coefficient of H2 in the electrolyte.

[0127] j k It can be obtained from the simplified KL equation (Equation 6):

[0128]

[0129] The exchange current density (j0) is the current at equilibrium, fitted by the Butler-Volmer (BV) equation (Equation 7). k The overpotential (η) can be used to determine:

[0130]

[0131] Where α is the charge transfer coefficient.

[0132] The value of j0 can also be obtained from the micro-polarization region, which is a region only a few millivolts away from the equilibrium potential. Within this narrow region, the diffusion component is negligible, and the kinetic current can be represented by the measured current. The BV equation can be expanded using Taylor's formula and simplified to Equation 8:

[0133]

[0134] Therefore, at lower overpotentials (±5mV or ±10mV), j0 can also be obtained from the slope of a linear fit of the micropolarized region.

[0135] For j under a certain overpotential (generally a relatively low overpotential of 50mV) k Alternatively, by normalizing j0 to the metal loading and ECSA, the specific activity j can be obtained. k,s and j k,m or j 0,s and j 0,m This allows for the assessment of the intrinsic electrocatalytic activity of the catalyst.

[0136] Electrochemical measurements of HOR catalysts are typically performed in a standard three-electrode system using an electrochemical workstation. The three electrodes generally consist of a working electrode, a reference electrode, and a counter electrode. Due to the low solubility of H2 in the electrolyte, a rotating disk electrode (RDE) testing apparatus is used for measurement.

[0137] The electrochemical performance of the first material Rh2Sb / CNT prepared in Example 1, the second material RhSb / CNT prepared in Example 2, the third material RhSb2 / CNT prepared in Comparative Example 1, and the fourth material Rh / CNT prepared in Comparative Example 2 were tested below. Meanwhile, a commercially available 20% Pt / C catalyst (purchased from Alfa Aessar) was purchased and named Pt / C. com , as a control sample.

[0138] Preparation of the working electrode: 1 mL of H2O / isopropanol / 5 wt% Nafion (purchased from Alfa Aessar) solution (volume ratio 75:25:2.5) was added to 1 mg of each of the above four materials and Pt / C. com After ultrasonic homogenization, a 1 mg / mL electrocatalyst ink was prepared. A certain volume of the electrocatalyst ink was uniformly dropped onto a glassy carbon electrode (GCE, purchased from Shanghai Yueci Electronic Technology Co., Ltd.). The loading of each catalyst prepared was approximately 12 μg, as determined by ICP-AES. Rh / cm 2 (Rh2Sb / CNT), 12μg Rh / cm 2 (RhSb / CNT), 12μg Rh / cm 2 (RhSb2 / CNT), 15μg Rh / cm 2 (Rh / CNT), 15μg Pt / cm 2 (Pt / Ccom), air-dried and ready for testing.

[0139] Electrochemical testing: In a standard three-electrode system at 20℃, RDE (0.196 cm / disk 2 Electrochemical tests were performed using a CHI 760E electrode connected to a saturated calomel electrode (SCE) with a saturated potassium chloride salt bridge and a graphite rod, which served as the reference and counter electrodes, respectively. Unless otherwise specified, all potentials were calculated to the reversible hydrogen electrode (RHE) and corrected for iR; all electrochemical tests were performed in 0.1 M KOH solution.

[0140] Performance test results

[0141] In a 0.1M KOH solution saturated with H2, linear sweep voltammetry (LSV) was performed at a rotation speed of 1600 rpm with a scan voltage range of -0.02 to 0.5 V vs. RHE and a scan rate of 5 mV / s. Polarization curves for each catalyst, normalized to the GCE area, were obtained, as shown below. Figure 21 As shown, at an overpotential of 80 mV vs. RHE, the current density of Rh2Sb / CNT rapidly reaches 2.8 mA cm⁻¹. disk -2 The current density of RhSb / CNT rapidly reaches 2.5 mA cm⁻¹. disk -2 The current density of RhSb2 / CNT is 1.3 mA cm⁻¹. disk -2 The current density of Rh / CNT is 1.2 mA cm⁻¹. disk -2 Pt / C com The current density is 1.8 mA cm⁻¹ disk -2 It is evident that Rh2Sb / CNT and RhSb / CNT both exhibit better performance than RhSb2 / CNT, Rh / CNT, and Pt / C. com Significantly higher anode current.

[0142] Figure 22 The logarithmic relationship between kinetic current density and potential is shown. Figure 22 It can be seen that Rh2Sb / CNT and RhSb / CNT at 20mV vs. RHE... k 2.18mA cm disk -2 and 1.67mA cm disk -2 RhSb2 / CNT, Rh / CNT and Pt / C com j at 20mV vs. RHE k 0.73mA cm disk -2 0.65mA cm disk -2 and 1.03mA cm disk -2 This indicates that Rh2Sb / CNT and RhSb / CNT have better performance than RhSb2 / CNT, Rh / CNT, and Pt / C. com The HOR reaction kinetics are significantly faster. Furthermore, the exchange current density (j0) can be obtained from the Tafel curve fitted to the BV equation.

[0143] In a 0.1M KOH solution saturated with H2, the rotational speed of the reactive gas desorption (RDE) was varied to 625, 900, 1225, 1600, 2025, and 2500 rpm, with a scanning voltage range of -0.02 to 0.5 V vs. RHE and a scan rate of 5 mV / s. The HOR polarization curves of the catalyst at different rotational speeds (625–2500 rpm) were obtained, and based on this data, the KL curve at 50 mV vs. RHE was also obtained. Figure 23 As shown. From Figure 23 It can be observed that the reciprocal of the current density (j -1 ) and the reciprocal of the square root of the rotational speed (ω) -1 / 2 The relationships between Rh2Sb / CNT, RhSb / CNT, RhSb2 / CNT, Rh / CNT, and Pt / C are linear. com The slopes of the KL curves were 4.56, 4.77, 5.41, and 4.32 cm, respectively. 2 mA -1 s -1 / 2 This is consistent with the theoretical value of the two-electron HOR process (4.87 cm⁻¹). 2 mA -1 s -1 / 2 The close proximity of ω indicates that the HOR reaction of the above catalyst is a two-electron transfer process. -1 / 2 Extrapolating to 0, we can calculate j at 50mV vs. RHE. k .

[0144] Cyclic voltammetry (CV) tests were conducted in a 0.1 M KOH solution saturated with N2, with scan potentials ranging from -0.005 to 0.6 V vs. RHE at a scan rate of 50 mV / s. The H2 content of different catalysts was determined by fitting and calculation. upd The desorption peak area can be used to obtain a histogram of ECSA, such as... Figure 24 As shown. It can be seen that Rh2Sb / CNT, RhSb / CNT, RhSb2 / CNT, Rh / CNT and Pt / C com The ECSA values ​​were 44.5, 42.1, 40.5, 31.9, and 50.2 m, respectively. 2 g PGM -1 .

[0145] To quantitatively compare the intrinsic activities of each catalyst, j0 and j k Through ECSA and noble metal loading mass normalization, respectively denoted as j 0,s j 0,m and j k,s j k,m .

[0146] Figure 25The exchange current density j of different catalysts, normalized by ECSA and noble metal supported mass, is given. 0,s and j 0,m A comparison plot at overpotentials of 50mV vs. RHE. It can be seen that for mass normalization j0(j 0,m ), Rh2Sb / CNT (0.32Amg) PGM -1 ) respectively compared to RhSb / CNT (0.25A mg PGM -1 ), RhSb2 / CNT (0.08 mg) PGM -1 ), Rh / CNT (0.06 mg) PGM -1 ) and Pt / C com (0.12A mg PGM -1 The values ​​are approximately 1.3, 4.0, 5.3, and 2.7 times higher for ECSA normalized j0(j 0,s The Rh2Sb / CNT ratio is 0.72 mA / cm². PGM -2 The value is much higher than that of RhSb / CNT (0.58 mA cm⁻¹). PGM -2 ), RhSb2 / CNT (0.20mA cm PGM -2 ), Rh / CNT(0.20mA cm PGM -2 ) and Pt / C com (0.30mA cm PGM -2 This indicates that the intrinsic activity of Rh2Sb / CNT is much higher.

[0147] Figure 26 The kinetic current density j of different catalysts, normalized by ECSA and noble metal supported mass, is given. k,s and j k,m Comparison plot at overpotentials of 50mV vs. RHE. Mass normalization of Rh2Sb / CNT. k (j k,m ) is 2.04A mg PGM -1 The values ​​are RhSb / CNT (1.44 mg). PGM -1 ), RhSb2 / CNT (0.14A mg) PGM -1 ), Rh / CNT (0.12A mg) PGM -1 ) and Pt / Ccom (0.27A mg PGM -1 The values ​​were 1.4, 14.6, 17.0, and 7.6 times higher than those of ECSAs. Furthermore, the normalized j values ​​for ECSAs... k (j k,s The value of Rh2Sb / CNT follows a trend: 4.57 mA cm PGM -2 RhSb / CNT(3.41mA cm) PGM -2 Pt / C com (0.69mA cm PGM -2 )>Rh / CNT(0.37mA cm PGM -2 RhSb2 / CNT(0.36mA cm) PGM -2 This further demonstrates that Rh2Sb / CNT is more efficient than RhSb / CNT, RhSb2 / CNT, and Pt / C. com It has more inherent HOR activity and faster kinetics.

[0148] Durability is another important indicator for evaluating the usefulness of catalysts in HOR. Rh₂Sb / CNT and Pt / C were selected. com With Rh / CNT catalyst, at an overpotential of 100 mV vs. RHE, and a rotation speed of 1600 rpm, the mixture was continuously operated for 12 h in a 0.1 M KOH solution saturated with H2. The decay of current over time was recorded, and the results are as follows: Figure 27 As shown, after continuous operation in H2-saturated 0.1 MkOH for 12 h, the Rh2Sb / CNT catalyst exhibited a slight degradation (23.3%) in activity. However, under the same conditions, Rh / CNT (74.6% loss) and Pt / C were observed to show significant deterioration. com The severe attenuation (70.3% loss) indicates that Rh2Sb / CNT is significantly inferior to Rh / CNT and Pt / C. com It has excellent stability.

[0149] Furthermore, since most of the H2 is supplied economically and efficiently through reforming fossil fuels, a small amount of CO impurities are inevitably mixed in during the hydrogen evolution process. Therefore, the CO tolerance of the catalyst is evaluated below in an H2 / 1000ppm CO atmosphere.

[0150] In a 0.1M KOH solution saturated with H2 / 1000ppm CO, the HOR LSV curves for different catalysts were obtained at a scanning speed of 1600 rpm, a scanning voltage range of -0.02–0.5 V vs. RHE, and a scanning rate of 5 mV / s. These curves were then compared with those obtained under the same H2-saturated conditions. Figures 28a-28e As shown. By Figures 28a-28e As can be seen, compared with the polarization curve of pure H2, the limiting current density of Rh2Sb / CNT and RhSb / CNT decreased by 4.9% and 2.2% respectively in the presence of 1000ppm CO, while the limiting current density of RhSb2 / CNT decreased by 27.5%. The limiting current density of Rh / CNT and Pt / C... com They were more likely to adsorb CO, with reductions of 51.5% and 73.8% respectively, indicating that their CO tolerance was lower than that of Rh2Sb / CNT and RhSb / CNT.

[0151] Similarly, Rh2Sb / CNT and Pt / C were selected. com With Rh / CNT catalyst, at an overpotential of 100 mV vs. RHE, and a rotation speed of 1600 rpm, the mixture was continuously operated for 12 h in a 0.1 M KOH solution saturated with H2 / 1000 ppm CO, and the current decay over time was recorded. Figure 29 As shown, under simulated conditions of H2 / 1000ppm CO, measured by chronoamperometry, Rh2Sb / CNT only decayed by 12.7% of its current density after 2000 s, while Rh / CNT and Pt / C... com The rapid decreases of 69.2% and 82.3% indicate that Rh2Sb / CNT exhibits excellent CO tolerance.

[0152] In summary, the CNT-loaded Rh prepared by this invention... x Sb y In binary intermetallic compounds, Rh x Sb y The nanoparticles are small in size, uniform in particle size, and well-dispersed, achieving a strict atomic stoichiometry and exhibiting excellent performance. They are highly active and stable binary IMC electrocatalyst materials. Among them, the catalytic activity of Rh2Sb / CNT is significantly higher than that of Rh / CNT and Pt / C. com It showed a 17-fold and 8-fold increase, demonstrating excellent HOR activity and stability, far superior to metallic Rh and commercial Pt / C. com The RhSb / CNT exhibits excellent stability and outstanding CO tolerance during use. Furthermore, it demonstrates very strong CO poisoning resistance and outstanding HOR catalytic activity, significantly outperforming metallic Rh and commercially available Pt / C. comThe performance of Rh2Sb / CNT and RhSb / CNT is excellent. They can be used as HOR catalysts, especially as anode HOR catalysts in alkaline exchange membrane fuel cells. Furthermore, the preparation method of this invention is simple and low-cost, which facilitates its widespread use.

[0153] Finally, it should be noted that the above embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Furthermore, it should be understood that after reading the technical content of this invention, those skilled in the art can make various modifications, alterations, or variations to the invention, and all such equivalent forms also fall within the scope of protection defined by the appended claims.

Claims

1. A type of Rh x Sb y / CNT material, characterized in that Rh supported on carbon nanotubes x Sb y Binary intermetallic compounds, wherein x:y = 1:1 or 2:

1.

2. The Rh as described in claim 1 x Sb y / CNT material, characterized in that The Rh x Sb y Binary intermetallic compounds belong to the orthorhombic crystal system with space group Pnma(62).

3. The Rh as described in claim 1 x Sb y / CNT material, characterized in that The Rh x Sb y In binary intermetallic compounds, the direction of electron transfer is from Sb to Rh.

4. The Rh according to any one of claims 1 to 3 x Sb y The preparation method of / CNT material includes the following steps: (1) Carbon nanotubes were ultrasonically dispersed in an ethanol aqueous solution, and then a RhCl3 / EtOH solution with a concentration of 0.1 mol / L was added and stirred for 10-60 min. NH4HCO3 was then added and stirring was continued for 2-10 h. The resulting suspension was centrifuged, washed, and freeze-dried to obtain a black solid. The black solid was then calcined at 600 °C for 1-3 h under a H2 / Ar reducing atmosphere and cooled to obtain Rh / CNT. The ratio of carbon nanotubes to Rh was 1.25-20 mmol of Rh per gram of carbon nanotubes. (2) The Rh / CNT is ultrasonically dispersed in deionized water to obtain an Rh / CNT suspension; SbCl3 is immersed in deionized water and ultrasonically dispersed to prepare an SbCl3 aqueous suspension; the SbCl3 aqueous suspension is mixed with the Rh / CNT suspension to obtain a mixed suspension, wherein the molar ratio of Rh to Sb in the feed is 2:1.8 or 1:1.2; (3) After stirring the mixed suspension for 30–90 min, evaporate and dry it at 80–120 °C, and collect the black precipitate; calcine the obtained black precipitate at 800 °C for 1–4 h under a H2 / Ar reducing atmosphere, and cool it to obtain the Rh. x Sb y / CNT material.

5. The Rh as described in claim 4 x Sb y The method for preparing CNT materials is characterized by... In step (1), the volume ratio of H2O to EtOH in the ethanol aqueous solution is 1:

1.

6. The Rh as described in claim 4 x Sb y The method for preparing CNT materials is characterized by... In step (1), the volume percentage of H2 in the H2 / Ar reducing atmosphere is 5%-40%.

7. The Rh as described in claim 4 x Sb y The method for preparing CNT materials is characterized by... In step (3), the volume percentage of H2 in the H2 / Ar reducing atmosphere is 5%-40%.

8. The Rh according to any one of claims 1 to 3 x Sb y Application of CNT materials as catalysts in the hydrogenation reaction under alkaline media.

9. The application as described in claim 8, characterized in that, The Rh x Sb y / CNT materials are used as HOR catalysts in alkaline exchange membrane fuel cells.

10. The application as described in claim 8, characterized in that, The Rh x Sb y Application of CNT materials as catalysts for resisting CO poisoning in the hydrogenation reaction under alkaline media.

Citation Information

Patent Citations

  • Preparation method of carbon ball loaded RhCo alloy electrocatalyst

    CN107230791A

  • Porous metal / cnt composite and method for manufacturing the same

    KR1020100128178A